Komponen dan Model Pengembangan Kurikulum PAI - Muhadi, Ihsan; Widyaningsih, Erna (Lembaga Yasin AlSys, 2025)
This study is motivated by the urgent need to develop an Islamic Religious Education (IRE) curriculum that responds to contemporary challenges—philosophical, psychological, and social. The objective is to identify the essential components and explore relevant models in IRE curriculum development. This research employs a library research method with a descriptive qualitative approach, gathering data from books, journals, and relevant academic documents. The analysis was conducted through deductive and comparative techniques. The results indicate that the components of the IRE curriculum include objectives, content/materials, learning strategies, and evaluation, all of which must be arranged systematically and integratively. The curriculum development models suitable for IRE include the administrative model, the grass roots model, and the demonstrative model. In conclusion, a comprehensive understanding of curriculum components and development models is crucial to producing an IRE curriculum that is contextual, adaptive, and relevant to both learners’ needs and societal development.